Transcranial Pulse Stimulation as a New Navigated Focal Brain Therapy for Vascular Cognitive Impairment: Case Report - Gunawan, Andrie; Tiksnadi, Amanda; Tunjungsari, Dyah; Kathy Putri Sari, Christine (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2024)
Introduction: To evaluate the cognitive function of vascular cognitive impairment (VCI) after transcranial pulse stimulation (TPS) sessions Case Report: TPS is a non-invasive brain stimulation method. Stimulation was administered using NEUROLITH TPS generator (Storz Medical AG) with 3 Hz ultrashort pulses at 0.25 mJ mm-2 energy density over 12 sessions (6000 pulses per session), three times/week. Target areas included the bilateral DLPFC (1600 pulses per hemisphere), parietal regions (P3, P4) (800 pulses per hemisphere), and precuneus (PCu) (1200 pulses). Cognitive function tests were conducted before the first and after the last TPS session, including MMSE, MoCa-Ina, 15 Boston Naming Test Patient, Digit Span, CERAD (Visuoconstruction, Delayed Memory, Recognition, Verbal Fluency), and Trail Making Test A & B. Discussion: Case 1 was a 48-year-old man with VCI and dysphasia post-stroke infarct (10 months prior), affecting the left caudate nucleus, left lentiform nucleus, and left internal capsule. The patient presented memory and executive function issues but preserved recognition. Case 2 was a 62-year-old man with VCI and anomic aphasia, following a cerebral infarction 5 months prior affected the left putamen, corona radiata, internal capsule, and globus pallidus. After 12 sessions, Case 1 showed amplification in working memory but had executive function challenges. Case 2 demonstrated improvement in immediate memory, recognition, and visuoconstruction, but had lingering issues with delayed verbal, visual memory, and executive function. Conclusion: TPS stimulation of areas for cognitive function appears to enhance memory, recognition, and other cognitive function. TPS may be a novel add‐on therapy for VCI post-stroke patients.